Exploring Stereotypes and Cultural References in Dubbed TV Comedies in the Spanish-as-a-Foreign-Language Classroom - Ogea Pozo, María del Mar; Botella Tejera, Carla; Bolaños García-Escribano , Alejandro (Íkala, Revista de Lenguaje y Cultura, 2023)
Streaming video-on-demand (SVoD) platforms have recently set out to produce an ever-increasing number of non-English-language films and tv series distributed worldwide. These, in turn, have become the perfect vehicle for disseminating cultural realities other than those from English-speaking countries. In this article, we endeavour to analyse the presence of stereotypes and cultural references in the English-dubbed version of the Spanish tv series Valeria (Benítez, 2020–present) and the way they travel through dubbing. To this end, we conducted a comparative study in which seven video excerpts from the English-dubbed version and their original Spanish version were shown to 57 native English-speaking participants from a British higher education institution, who shared a similar knowledge of Spanish as a foreign language. Specifically, we explored the participants’ overall perception of humorous passages, their identification of cultural references, their informed opinion on the translation techniques applied (and alternatives given), and their self-assessment of the metacognitive effort required. The findings show two aspects of learners: (a) overall, these learners were eager to maintain stereotypes and cultural references used for humorous purposes in audiovisual comedies, and (b) their understanding of these items often relies on audiovisual support. The findings offer an initial examination of English speakers’ cognitive and evaluative perception of Spanish comedies that have been dubbed in English and can be useful for translator training purposes.